Implementation of an Algorithm for the Estimation of the Sea Clutter Distribution and Parameters - Gato Martínez, Ismary; Machado Fernández, José Raúl; Jiménez Álvarez, Mónica (Ingeniería, 2017)
Sea clutter is the main interfering signal in radar systems. In order to develop appropriate strategies for clutter suppression, an algorithm able to identify the distribution of radar readings becomes necessary. By using several popular methods found in the related literature, the authors design an algorithm able to identify the clutter distribution and its corresponding parameters. The proposed solution, which included the widely used maximum likelihood method and the Kolmogorov-Smirnov statistic test, was implemented in a software application with an intuitive graphical interface. As a result, a viable instance of the algorithm became available for educational and research purposes, particularly as a comparative base for estimating the effect of the size increase in the sample set when estimating the probability distribution.